2021
DOI: 10.1093/schbul/sbab123
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Deliberate Self-harm and Suicide Among Adolescents and Young Adults With First-Episode Psychosis

Abstract: Little is known about the risk factors for deliberate self-harm (DSH) and suicide among adolescents and young adults with first episode psychosis (FEP) and the longitudinal course of DSH following the initial onset of illness. This study identifies risk factors for DSH and suicide death among Medicaid-covered adolescents and young adults with FEP along with the periods of greatest risk for DSH after diagnosis. A retrospective longitudinal cohort analysis was performed using Medicaid claims data merged with dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 49 publications
1
22
0
2
Order By: Relevance
“…Age and perceived stress emerged as two of the most relevant variables related to suicidal behaviours. Age was related to suicidal ideation and suicidal attempt, what gives further support to the importance of suicide awareness in young populations (Barrett et al, 2010; Bertelsen et al, 2007; Moe et al, 2021; Pelizza et al, 2020; Pelizza et al, 2021; Suokas et al, 2010). Stress was linked to suicidal ideation and an increased presence of suicidal risk, as previous studies have reported (Abdollahi et al, 2015; Chen & Kuo, 2020; Klonsky et al, 2018).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Age and perceived stress emerged as two of the most relevant variables related to suicidal behaviours. Age was related to suicidal ideation and suicidal attempt, what gives further support to the importance of suicide awareness in young populations (Barrett et al, 2010; Bertelsen et al, 2007; Moe et al, 2021; Pelizza et al, 2020; Pelizza et al, 2021; Suokas et al, 2010). Stress was linked to suicidal ideation and an increased presence of suicidal risk, as previous studies have reported (Abdollahi et al, 2015; Chen & Kuo, 2020; Klonsky et al, 2018).…”
Section: Discussionmentioning
confidence: 79%
“…Patients with psychotic disorders, and especially those diagnosed with schizophrenia, have an increased risk of suicide compared to the general population (Hawton et al, 2005). Around 30%-40% of people with psychosis present suicidal ideation (Fenton et al, 1997;Fialko et al, 2006;Moe et al, 2021), between 20% and 40% have had at least a suicide attempt (Harkavy-Friedman, 2006), and it is estimated that between 4% and 13% will consummate a suicide attempt (De Hert et al, 2001;Simms et al, 2007). Currently, there is sufficient evidence that indicates that suicide is the leading cause of premature death in schizophrenia (Saha et al, 2007).…”
mentioning
confidence: 99%
“…Suicide is one of the most devastating outcomes for individuals with psychosis, with rates that are 13× greater than the general population (Too et al, 2019). Several studies have shown that suicide risk is greatest during the early stages of illness (e.g., Moe et al, 2021; Ventriglio et al, 2016). Additionally, suicide risk is elevated among individuals at CHR‐P, with 66% reporting recent suicidal ideation and 11% reporting lifetime suicidal behaviour (Taylor et al, 2015).…”
mentioning
confidence: 99%
“…Individuals with schizophrenia are at particularly high-risk for suicide (Caldwell & Gottesman, 1990), with suicide rates that are approximately 13 times greater than the general population (Too et al, 2019). A number of studies have demonstrated that suicide risk among individuals with schizophrenia is greatest during the first few years, or even months, after receiving a diagnosis (e.g., Coentre et al, 2017; Moe et al, 2021; Nordentoft et al, 2015; Pompili et al, 2011; Ventriglio et al, 2016). There is also emerging evidence that suicide risk might develop before illness onset, with studies showing elevated rates of suicidal thoughts and behaviors among individuals deemed clinical high-risk (CHR) for psychosis (e.g., Haining et al, 2021; Pelizza et al, 2020; Taylor et al, 2015).…”
mentioning
confidence: 99%
“…Individuals with schizophrenia are at particularly high-risk for suicide (Caldwell & Gottesman, 1990), with suicide rates that are approximately 13 times greater than the general population (Too et al, 2019). A number of studies have demonstrated that suicide risk among individuals with schizophrenia is greatest during the first few years, or even months, after receiving a diagnosis (e.g., Coentre et al, 2017;Moe et al, 2021;Nordentoft et al, 2015;Pompili et al, 2011;Ventriglio et al, 2016).…”
mentioning
confidence: 99%